Visualization of conventional outflow tissue responses to netarsudil in living mouse eyes - Li,G; Mukherjee,D; Navarro,I; Ashpole,NE; Sherwood,JM; Chang,J; Overby,DR; Yuan,F; Gonzalez,P; Kopczynski,CC; Farsiu,S; Stamer,WD (European Journal of Pharmacology, 2016)
Visual impairment due to glaucoma currently impacts 70 million people worldwide. While disease progression can be slowed or stopped with effective lowering of intraocular pressure, current medical treatments are often inadequate. Fortunately, three new classes of therapeutics that target the diseased conventional outflow tissue responsible for ocular hypertension are in the final stages of human testing. The rho kinase inhibitors have proven particularly efficacious and additive to current therapies. Unfortunately, non-contact technology that monitors the health of outflow tissue and its response to conventional outflow therapy is not available clinically. Using optical coherence tomographic (OCT) imaging and novel segmentation software, we present the first demonstration of drug effects on conventional outflow tissues in living eyes. Topical netarsudil (formerly AR-13324), a rho kinase/ norepinephrine transporter inhibitor, affected both proximal (trabecular meshwork and Schlemm’s Canal) and distal portions (intrascleral vessels) of the mouse conventional outflow tract. Hence, increased perfusion of outflow tissues was reliably resolved by OCT as widening of the trabecular meshwork and significant increases in cross-sectional area of Schlemm’s canal following netarsudil treatment. These changes occurred in conjunction with increased outflow facility, increased speckle variance intensity of outflow vessels, increased tracer deposition in conventional outflow tissues and decreased intraocular pressure. This is the first report using live imaging to show real-time drug effects on conventional outflow tissues and specifically the mechanism of action of netarsudil in mouse eyes. Advancements here pave the way for development of a clinic-friendly OCT platform for monitoring glaucoma therapy.